Survei Antropometri Tubuh dan Kondisi Fisik Atlet Atletik Kota Kediri - Zulviyanto, Rhosera Risty Zulviyanto (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2024)
Athletics is an activity that involves the body with basic dynamic movements, namely: walking, running, throwing and jumping. This study aims to analyze the anthropometric body shape and physical condition of PASI athletic athletes in Kediri City. Data was collected using observation techniques and analyzed using descriptive statistics. In the men's group, there were 29 athletes and in the women's group, there were 23 athletes. Body anthropometry results for height measurements were 48% and 65% in the fair category, weight measurements were 93% and 83% in the excellent category, and leg length measurements were 31% and 39%. categorized as sufficient. In terms of physical condition, the explosive power component of the leg muscles in the standing board jump test resulted in 38% and 83% in the poor and very good categories, in the vertical jump test 52% and 83% in the sufficient and very good categories, in the vertical jump test the results were in the moderate and very good categories, and the explosive power in the arm muscles in basketball throwing was 66% and 39% was categorized as sufficient, the cardiovascular endurance component using the bleep test was 55% and 52% categorized as adequate and good, and the flexibility component using the sit and reach test was 45% and 48% categorized as sufficient. The results of the study concluded that the female group was more dominant in getting better results than the male group